Exploring sprint kinematics in American football athletes after anterior cruciate ligament reconstruction - Ito, N.; Lin, Y.-C.; Martin, J. A.; Blemker, S. S.; Opar, D. A.; Kliethermes, S. A.; Heiderscheit, B. C.; HAMIR Consortium Investigators. (Scandinavian Journal of Medicine & Science in Sports, 2026)
The purpose of this study was to compare stance time and knee joint kinematics between limbs during sprinting in Division-1 collegiate American football athletes with a history of anterior cruciate ligament reconstruction (ACLR). This secondary analysis used data from an ongoing multicenter prospective cohort study of NCAA Division-1 American football athletes. Sprint biomechanics were collected using wearable inertial measurement units during on-field, maximal effort overground sprints. Knee kinematic variables of interest included stance time, knee flexion angle at initial contact, peak knee flexion angle, and knee flexion excursion during the stance phase from 2 to 5 strides near peak sprinting speed. Linear mixed effects models were used to evaluate the main effects of limb (involved vs. uninvolved), time from surgery, and their interaction on variables of interest, adjusted for peak sprint speed. Twenty male athletes (mean age: 21.2 ± 1.3 years; time from surgery: 28.0 ± 18.5 months) were fully participating in American football without limitations at the time of testing and met inclusion criteria. No significant limb × time interactions (p = 0.3-0.60) or main effects of limb (p = 0.23-0.84) or time (p = 0.08-0.84) were observed for any of our variables of interest. Division-1 American football athletes approximately 2 years post-ACLR did not demonstrate asymmetrical knee joint kinematics or stance time during sprinting. While gait asymmetries are commonly observed after ACLR during submaximal walking and running, these differences may diminish at high effort levels required during sprinting. IMU-based methods provide a clinically feasible approach for assessing on-field sprint biomechanics in athletes after ACLR.